Agency: The Force and Compass of Transformation. (April 2022) - Green, Larry
Mezirow's theory of transformative learning presupposes agency. Agency is the means by which the limitations of an inadequate meaning perspective are transcended. It is the creative activity necessitated by an encounter with a disorienting dilemma. This implies that transformation cannot be achieved from within the existent meaning perspective. It can only be exercised from outside that constellation of constructs. This depends on the person dissociating from that perspective in order to enter a groundless state where originary thought is possible. In that state, they have access to an impersonal consciousness. That impersonal consciousness, which constructed the problematic meaning perspective, is now utilized for designing a more adequate one. These processes are accompanied by associated affects. For example, anxiety is the affect associated with groundlessness whereas depression with the lack of agency. I suggest that agency arises when the situation demands it and falls away after the dilemma has been addressed.